Effect of trimetazidine on oxidative stress parameters in patients on CAPD - Celiker, H; Ihsan, GA; Ilhan, N; Dogukan, A; Aygen, B (Oxford Univ Press, 2005)
[Abstract Not Available]
42nd Annual Meeting of the European-Renal-Association/European-Dialysis-and-Transplant-Association (ERA-EDTA) -- JUN 04-07, 2005 -- Istanbul, TURKEY